Artificial intelligence surveillance and the right to privacy in Vietnam a human security policy - Nguyen Nam Trung (Otoritas : Jurnal Ilmu Pemerintahan, 2025)
The rapid expansion of artificial intelligence (AI)–enabled surveillance has become a central feature of contemporary governance, enhancing public security while raising serious concerns for the right to privacy. This article examines AI surveillance in Vietnam through the combined lenses of human security and Article 17 of the International Covenant on Civil and Political Rights (ICCPR). Using doctrinal legal analysis and focused comparative evaluation, the study analyses how AI surveillance practices—such as facial recognition, biometric profiling, and behavioural analytics—generate cumulative privacy risks, including informational opacity, behavioural chilling, algorithmic bias, and institutional accountability deficits. It further assesses whether Vietnam’s existing legal framework, particularly the Law on Cybersecurity and Decree 13/2023/NĐ-CP, satisfies ICCPR standards of legality, legitimate aim, necessity, proportionality, and effective oversight. The findings reveal significant normative and institutional gaps. Drawing on comparative insights from the EU’s GDPR and South Korea’s PIPA, the article proposes a phased and context-sensitive reform pathway to strengthen privacy protection while supporting Vietnam’s digital transformation and national-security objectives.